2000
DOI: 10.1103/physrevlett.84.5288
|View full text |Cite
|
Sign up to set email alerts
|

Precise Measurement ofdpElastic Scattering at 270 MeV and Three-Nucleon Force Effects

Abstract: The cross section, the deuteron vector A(d)(y) and tensor analyzing powers A(ij), the polarization transfer coefficients K(y('))(ij), and the induced polarization P(y(')) were measured for the dp elastic scattering at 270 MeV. The cross section and A(d)(y) are well reproduced by Faddeev calculations with modern data-equivalent nucleon-nucleon forces plus the Tucson-Melbourne three-nucleon force. In contrast, A(ij), K(y('))(ij), or P(y(')) are not described by such calculations. These facts indicate the deficie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
123
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 152 publications
(130 citation statements)
references
References 32 publications
7
123
0
Order By: Relevance
“…These two effects usually compete, and therefore * izabela.ciepal@uj.edu.pl the net effects of including the isobar in the potential are smaller than for approaches with the phenomenological 3NF's. When the chiral perturbation theory (ChPT) is used at the next-to-next-to-leading order (NNLO), the 3N contributions arise naturally, fully consistently with the NN force terms [4].The long-range electromagnetic component of the NN interaction was successfully implemented in CC formalism [5,6] as well as in the calculations [7] based on the AV18 NN potential combined with the Urbana IX 3NF.Besides the binding energies of the light nuclei, the importance of the 3NF was experimentally confirmed on the basis of the data originating from the nucleon-deuteron elastic scattering process [8][9][10][11][12][13][14][15][16][17]. In general, inclusion of the 3NF component improves the description of the cross-sectional data.…”
mentioning
confidence: 76%
See 1 more Smart Citation
“…These two effects usually compete, and therefore * izabela.ciepal@uj.edu.pl the net effects of including the isobar in the potential are smaller than for approaches with the phenomenological 3NF's. When the chiral perturbation theory (ChPT) is used at the next-to-next-to-leading order (NNLO), the 3N contributions arise naturally, fully consistently with the NN force terms [4].The long-range electromagnetic component of the NN interaction was successfully implemented in CC formalism [5,6] as well as in the calculations [7] based on the AV18 NN potential combined with the Urbana IX 3NF.Besides the binding energies of the light nuclei, the importance of the 3NF was experimentally confirmed on the basis of the data originating from the nucleon-deuteron elastic scattering process [8][9][10][11][12][13][14][15][16][17]. In general, inclusion of the 3NF component improves the description of the cross-sectional data.…”
mentioning
confidence: 76%
“…Besides the binding energies of the light nuclei, the importance of the 3NF was experimentally confirmed on the basis of the data originating from the nucleon-deuteron elastic scattering process [8][9][10][11][12][13][14][15][16][17]. In general, inclusion of the 3NF component improves the description of the cross-sectional data.…”
mentioning
confidence: 85%
“…More recently it has also been suggested that minima and polarization observables of Nd elastic scattering at intermediate energies are sensitive to V ijk , and may be used to refine models of V ijk [59][60][61]. Thus further improvements in realistic models of V ijk may be possible by a simultaneous fit to Nd scattering observables and nuclear binding energies.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…The large discrepancy in the minimum of the elastic scattering cross section obtained with NN forces only seen for energies above ≈ 60 MeV is removed for energies below ≈ 140 MeV when 3NF's are included which reproduce the experimental triton binding energy [17,16] (see left panels of Figs.1 and 2). A similar behavior shows up for the high energy deuteron vector analyzing power A y (d) [16,18,19,20]. But there are many spin observables for which large 3NF effects are predicted and where the TM and the Urbana IX do not reproduce the data [16].…”
Section: Reactions In the 3n Continuummentioning
confidence: 77%